This is your brain on death: a comparative analysis of a near-death experience and subsequent 5-Methoxy-DMT experience - Michael, Pascal; Luke, David; Robinson, Oliver (Frontiers in Psychology, 2023)
Introduction: Much research has focused on the modelling of the near-death experience (NDE) by classical and atypical psychedelics, whereas no study has yet been reported on the relationship between the experience of potent, endogenous psychedelic drug 5-Methoxy-DMT (5MeO-DMT) and the NDE. This article presents a case study of an individual popularly documented to have had a profound near-death experience during coma precipitated by bacterial meningoencephalitis, as well as subsequently experiencing 5MeO-DMT. Methods: A semi-structured interview was conducted with the subject concerning his NDE and 5MeO-DMT experience. A basic thematic analysis was performed on both the original text describing the near-death experience, as well as on the interview which mainly focused on the latter 5MeO-DMT experience. This analysis is organised into both the similar and different emergent themes between the two states, including, importantly, the personal perceptions as to similarities and differences held by the experiencer. Results: There is a very high level of comparability between the original NDE and psychedelic experiences in general, including entering other worlds, meeting menacing or benevolent entities, synaesthesia, perinatal regression, and lucid dream-like properties. Much comparability was also identified with the 5MeO-DMT experience, in particular the major mystical experiential domains, such as ego dissolution, but especially transcendence of time and space. This being so, a small constellation of themes (life review, the deceased, the threshold) were present in the experient’s NDE, while not in the 5MeO-DMT nor highly reproducible with psychedelics generally – and thus are more unique to near-death experiences. Discussion: Despite such resonances, the participant asserted that his NDE and psychedelic experiences were insufficiently similar to warrant any explanation by endogenous psychedelics. Several mechanisms of the NDE are discussed, including lucid dreams, perinatal regression, but focusing on the, duly caveated, speculation that unique aetiology of bacterial meningoencephalitis of the neocortex may enact similar down-stream neural activity as that initiated by pyramidal neuronal activation by psychedelic agents.